Life Cycle Assessment of End-of-Life Tire Disposal Methods and Potential Integration of Recycled Crumb Rubber in Cement Composites - Girts Kolendo; Viktoria Voronova; Girts Bumanis; Aleksandrs Korjakins; Diana Bajare (Applied Sciences)
Globally, 1.5 billion annual tire outputs generate a substantial volume of end-of-life tires (ELTs), creating significant environmental challenges. Despite increased recovery rates, ELT management costs in Europe underscore the need for proactive strategies to mitigate environmental and health risks. This study comprehensively evaluates the environmental impact of disposal methods, including landfilling, incineration, and crumb rubber production, using Life Cycle Assessment (LCA) via the OpenLCA software 2.0.2. While incineration is sometimes identified as a disposal method, unprocessed scrap tires have potential applications in civil engineering that can better align with sustainability goals. Detailed ELT composition analysis reveals significant recycling potential, with car and truck tires containing 10–20% steel fiber content, less than 1–8% textile fibers, and approximately 80% natural and synthetic rubber content. Recycling 1 ton of ELTs saves an estimated 1.4–1.6 tons of CO2 Eq. compared to incineration. Mechanical recycling and application of recycled crumb rubber in concrete show significant environmental advantages, reducing mass density by approximately 55% and enhancing ductility by up to 40%, according to material testing results. These properties make crumb rubber particularly suitable for acoustic and resilient applications. Additionally, its elasticity and durability offer effective solutions for shoreline reinforcement, mitigating erosion and providing stability during flooding events. When used as a replacement for river sand in cement composites, crumb rubber contributes to a 24.06% reduction in CO2 emissions, highlighting its potential for environmentally friendly construction.